2-Aminophenolate ligands for phosphorus(v): a lithium salt featuring the chiral [P(OC6H4NR)3]− anion. Issue 35 (1st August 2018) - Zhan, Chuantian; Han, Zeyu; Patrick, Brian O.; Gates, Derek P.
Abstract : The reaction of PCl5 with 2-aminophenols affords phosphoranes, P(OC6 H4 NR)2 (OC6 H4 NHR) (R = Me, Ph, C6 F5 ) which are precursors to M[P(OC6 H4 NR)3 ] (M = Li or K). Abstract : Phosphoranes P(OC6 H4 NR)2 (OC6 H4 NHR) [R = Me (2a ), Ph (2b ), C6 F5 (2c )] were synthesized by treating PCl5 with the respective 2-aminophenol derivative (1a–c, 3.1 equiv.). In one instance, an intermediate species, P(OC6 H4 NR)2 Cl [R = Me (3a )], was isolated and structurally characterized. Deprotonation of the amine moieties (–N H̲ R) in phosphoranes2a and2b with a strong alkali–metal base ( e.g. n -BuLi) in the presence of a strong-donor solvent ( e.g. THF) afforded salts composed of the hexacoordinate P(v )-anions [P(OC6 H4 NR)3 ] − (R = Me, [4a ] − ; Ph, [4b ] − ). Employing precursor2a, the salt Li(THF)3 fac -[4a ] − was isolated. The X-ray crystal of each enantiomer of [4a ] − was determined and, to our knowledge, represents the first structurally characterized example of a salt containing a hexacoordinate P(v )N3 O3 anion featuring P(v )–N bonds.